Caloric Restriction Dramatically Stalls Lesion Growth in Mice With Induced Endometriosis. (July 2018) - Yin, Bo; Liu, Xishi; Guo, Sun-Wei
Caloric restriction (CR) has been demonstrated to have many health-beneficial effects in many species, but whether CR can impede the development of endometriosis is unknown. To test the hypothesis that CR can impede the growth of endometriotic lesions and fibrogenesis, we conducted 2 experiments. In experiment 1, 20 female Balb/C mice were randomly assigned to either ad libitum (AL) group that was fed AL or to CR group that was fed 30% less calories than that of AL mice. Two weeks after the implementation of the dietary intervention, endometriosis was induced by intraperitoneal injection of endometrial fragments. Two weeks after the induction, all mice were sacrificed and their lesion samples were evaluated. In experiment 2, another 20 mice were used and CR was implemented 2 weeks after induction of endometriosis and lasted for 4 weeks. Caloric restriction instituted before the induction of endometriosis reduced the lesion weight by 88.5%, whereas CR implemented well after lesions were established reduced the lesion weight by 93.0%. In both cases, CR significantly increased staining levels of markers of autophagy but reduced proliferation, angiogenesis, steroidogenesis, and fibrosis in lesions as compared with the AL group. Consequently, CR, instituted either before or after the induction of endometriosis, dramatically curbs the growth of endometriotic lesions and fibrogenesis through multiple mechanisms. Caloric restriction and CR mimetics, a family of compounds mimicking the beneficial effect of CR, even when instituted well after lesions are established, may stall the development of endometriosis. Given the scarcity in research on how lifestyle can impact on the development of endometriosis, our study should hopefully stimulate more research in this area.